Effects of six weeks of chronic sleep restriction with weekend recovery on cognitive performance and wellbeing in high-performing adults. Issue 8 (25th February 2021) - Smith, Michael G; Wusk, Grace C; Nasrini, Jad; Baskin, Pamela; Dinges, David F; Roma, Peter G; Basner, Mathias
Abstract: Chronic sleep loss is associated with escalating declines in vigilant attention across days of sleep restriction. However, studies exceeding 2 weeks of chronic sleep loss are scarce, and the cognitive performance outcomes assessed are limited. We assessed the effects of 6 weeks of chronic sleep restriction on a range of cognitive domains in 15 high-performing individuals (38.5 ± 8.2 years, 6 women) confined to small space in groups of 4. Sleep opportunities were limited to 5 h on weekdays and 8 h on weekends. Individual sleep–wake patterns were recorded with actigraphy. Neurobehavioral performance was assessed in evenings with Cognition, a computerized battery of ten tests assessing a range of cognitive domains. There were some small to moderate effects of increasing sleep debt relative to pre-mission baseline, with decreases in accuracy across cognitive domains (standardized β = –0.121, p = 0.001), specifically on tests of spatial orientation (β = –0.289, p = 0.011) and vigilant attention (β = –0.688, p < 0.001), which were not restored by two nights of weekend recovery sleep. Cognitive and subjective decrements occurred despite occasional daytime napping in breach of study protocol, evening testing around the circadian peak, and access to caffeine before 14:00. Sensorimotor speed, spatial learning and memory, working memory, abstraction and mental flexibility, emotion identification, abstract reasoning, cognitive throughput, and risk decision making were not significantly affected by sleep debt. Taken together with modest lower subjective ratings of happiness and healthiness, these findings underline the importance of sufficient sleep, on both an acute and chronic basis, for performance in selected cognitive domains and subjective wellbeing in operationally relevant environments.